2003
DOI: 10.1021/jo020647x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of (C6F5)3B−N-Heterocycle Complexes. 1. Generation of Highly Acidic sp3Carbons in Pyrroles and Indoles

Abstract: The reaction of pyrroles and indoles with B(C(6)F(5))(3) and BCl(3) produces 1:1 B-N complexes containing highly acidic sp(3) carbons, for example, N-[tris(pentafluorophenyl)borane]-5H-pyrrole (1) and N-[tris(pentafluorophenyl)borane]-3H-indole (2), that are formed by a new formal N-to-C hydrogen shift, the mechanism of which is discussed. With some derivatives, restricted rotation around the B-N bond and/or the B-C bonds was observed by NMR techniques, and some rotational barriers were calculated from experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
49
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 45 publications
(49 reference statements)
8
49
0
Order By: Relevance
“…The 13 C NMR signal which correlates with these protons (d 76.4) also did not couple to phosphorus. These observations are consistent with the presence of acidic sp 3 protons in 5-membered N-heterocyclic compounds [18,19]. The 1 H NMR signals for the diastereotopic CH 2 P group were found as two multiplets centred at d 2.51 and 2.74; the corresponding 13 C signal appears as a doublet (J C-P = 26.6 Hz) and its coupling pattern is, as expected, altered in the 1 H{ 31 P} NMR spectrum (these 1 H NMR signals do not in fact become simple doublets of doublets as a small coupling exists between this ABX system and the AB methylene system situated on the 3-position of the pyrrole ring, as shown by 2D COSY NMR).…”
Section: H/ 1 H Correlation Experimentssupporting
confidence: 88%
See 1 more Smart Citation
“…The 13 C NMR signal which correlates with these protons (d 76.4) also did not couple to phosphorus. These observations are consistent with the presence of acidic sp 3 protons in 5-membered N-heterocyclic compounds [18,19]. The 1 H NMR signals for the diastereotopic CH 2 P group were found as two multiplets centred at d 2.51 and 2.74; the corresponding 13 C signal appears as a doublet (J C-P = 26.6 Hz) and its coupling pattern is, as expected, altered in the 1 H{ 31 P} NMR spectrum (these 1 H NMR signals do not in fact become simple doublets of doublets as a small coupling exists between this ABX system and the AB methylene system situated on the 3-position of the pyrrole ring, as shown by 2D COSY NMR).…”
Section: H/ 1 H Correlation Experimentssupporting
confidence: 88%
“…However, with B(C 6 F 5 ) 3 they give the catalytically active zwitterionic products 5a (R = Ph) and 5c (R = Cy), respectively. Some time ago Erker et al reported the abstraction of a pyrrolate ligand from Cp 2 ZrMe(NC 4 H 4 ) by B(C 6 F 5 ) 3 to give the [(1-pyrrolyl)B(C 6 F 5 ) 3 ] À anion [16] and synthesized 5H-pyrrole-B(C 6 F 5 ) 3 complex by acidification of (Et 2 O) 2 Li[(1-pyrrolyl)B(C 6 F 5 ) 3 ] [17], while Resconi and co-workers undertook a detailed study of the reaction of B(C 6 F 5 ) 3 with pyrroles, indoles, imidazoles and pyrazoles [18][19][20]. In all these cases, with the exception of N-alkyl pyrroles, the boron adds to the nitrogen atom.…”
Section: H/ 1 H Correlation Experimentsmentioning
confidence: 99%
“…[30] The ammonia, aniline, and diphenylamine adducts of B(C 6 F 5 ) 3 [31] are deprotonated by ItBu to generate ionic complexes 3-5, respectively, which is analogous to reaction with dihydrogen (Scheme 3).…”
mentioning
confidence: 99%
“…of B(C 6 F 5 ) 3 gave quantitative and instantaneous conversion to the 5 H ‐pyrrole · B(C 6 F 5 ) 3 complexes and 3 H ‐indole · B(C 6 F 5 ) 3 complexes (Scheme ). Most of these complexes were formed quantitatively and instantaneously, irrespective of the solvent or the order of addition 14c…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the imminic double bond combined with the presence of the strong electron‐withdrawing B(C 6 F 5 ) 3 Lewis acid generates quite a strong acidity of the proton(s) on the sp 3 C(3) or C(5). For example, 1 and 2 react with NEt 3 to give quantitatively the [B(1‐pyrrolyl)(C 6 F 5 ) 3 ][HNEt 3 ] salt ( 1a ) and the [B(1‐indolyl)(C 6 F 5 ) 3 ][HNEt 3 ] salt ( 2a ) respectively (Scheme ) 14b,c. In addition to 1a and 2a , we obtained the salts [B(2‐methyl‐indolyl)(C 6 F 5 ) 3 ][HNEt 3 ] ( 3a ), [B(3‐methyl‐indolyl)(C 6 F 5 ) 3 ][HNEt 3 ] ( 4a ), [B(5‐methoxy‐indolyl)(C 6 F 5 ) 3 ][HNEt 3 ] ( 6a ), [B(2,5‐dimethyl‐1‐pyrrolyl)(C 6 F 5 ) 3 ][HNEt 3 ] ( 9a ), [B(2‐ethyl‐1‐pyrrolyl)(C 6 F 5 ) 3 ][HNEt 3 ] ( 10a ) and [B(imidazolyl)(C 6 F 5 ) 3 ][HNEt 3 ].…”
Section: Resultsmentioning
confidence: 99%